A influência das decisões judiciais do Supremo Tribunal Federal na contabilidade das empresas: análise dos critérios do CPC 25 para o reconhecimento das provisões e contingências de processos judiciais tributários sob a perspectiva do julgamento do STF, nos Recursos Extraordinários 949.297 (Tema 881) e 955.227 (Tema 885) - Santana, Alexsander (2024)
The Technical Pronouncement CPC 25 provides guidance on the recognition, measurement and disclosure of provisions, contingent liabilities and contingent assets. The objective of this work is to analyze the accounting practices adopted by Brazilian companies regarding the accounting of provisions, passive and active contingencies of tax disputes that have already become final and unappealable, specifically regarding the discussion related to the unconstitutionality of the CSLL, after the judgment of Extraordinary Appeals 949.297 (STF Theme 881) and 955.227 (STF Theme 885) in the year 2023, which made the institution of res judicata more flexible in tax matters, disadvantaging all taxpayers. The stance adopted by the publicly traded company Grupo Pão de Açúcar – GPA was highlighted in its financial projections, our results projections are similar to all companies, publicly or privately held, and which are in the same condition. The methodology used was descriptive-exploratory. Research was carried out with the purpose of analyzing the application of CPC 25 criteria in the classification of provisions and contingencies in the company's accounting evidenced here. Considering the risks and uncertainties of the demand, the classification in the Financial Statements is carried out according to the experience of the professionals, considering that there is no standard determining, in a clear and objective way, the “probable, possible and remote” classification of procedural demands to be recorded in the accounts. Since these records are made using subjective criteria, the same accounting fact is specified differently, improving or worsening the result, creating advantages over companies that apply different classifications